STRUKTURASI PRAKTIK KEAGAMAAN ANAK DALAM KELUARGA MULTIAGAMA: STUDI FENOMENOLOGI PADA KELUARGA DI KOTA BEKASI - Nathacha Nathacha; Agus Machfud Fauzi (Jurnal Ilmiah Sosiologi Agama (JISA), 2025)
This research focuses on uncovering Anthony Giddens' duality of structure process in the religious practices of children in interfaith families, specifically how the dialectical interaction between child agency and religious structure reproduces or transforms those practices. The study utilizes a qualitative approach with Alfred Schutz's phenomenology design to capture subjective meaning, which is then theoretically analyzed using Anthony Giddens' Structuration Theory to understand the dialectical interaction between the parents' religious structure and the children's agency. Findings indicate that the family's religious structure is asymmetrical, dominated by the Mother (Islam) through resource control and dual legitimation (theological-pragmatic), which is reinforced by the Father's (Buddhist) strategic withdrawal. The children, as shrewd agents, realize their practices in the form of "distant obedience"; they use discursive consciousness to prioritize relational harmony, while practical consciousness reproduces the structure through ritual routinization. Simultaneously, this practice reproduces the dominant ritual structure, but also transforms the family's signification, shifting the meaning of religion from exclusive dogma toward universal ethics and tolerance, which is key to family resilience.